A study on length of stay and its predictors among dengue patients in a tertiary care institute in Lucknow - Mishra, Sandhya; Chopra, Deepak; Jauhari, Nidhi; Ahmad, Ausaf (International Journal Of Community Medicine And Public Health, 2019)
Background: Dengue virus infection is a growing health problem and is prevalent throughout India. Research focusing on length of hospital stay and its predictors is scarce from India. This is important considering the burden of the disease during epidemics and impact on hospital admissions. Hence the study was conducted with the objectives to find out the factors influencing the length of stay in hospital of dengue patients. Methods: A cross sectional retrospective observational study conducted at a tertiary care hospital from August 2016 to October 2016. Data was retrieved from case sheets at Medical Record Department of 350 lab confirmed adult dengue patients admitted in the hospital. Results: The majority of patients admitted were of economically productive age group of 18-45 years and males indicating the occupational exposure to the vector of dengue. The study found that majority had length of stay of less than a week and as age increases the length of stay also increases (statistically significant). The nil case fatality and lesser number of mean days of symptoms before admission possibly indicate that early arrival of patients to hospital can lead to very low fatality rates. Further research required to find out the other predictors of length of stay. Conclusions: The study concludes that the dengue affects the economically productive age group and more males thereby indicating occupational exposure to the vector. The age of the patient can be used as an indicator to the length of stay in the hospital.